Effect of Current Ratio and Return on Asset on Company Value (Case Study on Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2018-2020) - Silaen*, Karina; Maduwu, Lilis Dariyanti; Zebua, Adiwima (Riwayat: Educational Journal of History and Humanities, 2023)
This research was conducted to determine the effect of current ratio and return on assets on company value. This research uses quantitative methods. In this study, the population is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange in 2018-2020. Sample sampling technique using purposive sampling technique using several criteria. The data analysis technique uses classical assumption test, multiple linear regression analysis test, T test, F test and coefficient of determination (R2) test using SPSS application version 16. From the results of the study shows that the results of the T test, the current ratio variable has an effect but is not significant on the value of the company and the results of the T test, the variable Return On Asset on the value of the company has an effect and is significant to the value of the company. And from the results of the study shows that the results of the F test together with current ratio and return on assets have an effect and are significant on the value of the company.